Stress Analysis and Integrity Assessment of Offshore Gas Production Piping Systems Using CAESAR II and ASME B31.3 - Edi Sutoyo; Muhammad Salas Hakim; Budi Hartono; Hablinur Al Kindi; Setya Permana Sutisna (Journal of Applied Science and Advanced Engineering, 2026)
Offshore gas production piping systems operate under high-pressure and elevated-temperature conditions, requiring accurate stress analysis to verify code compliance and ensure reliable structural performance. This study investigates the stress behavior of a piping system connecting a production well to a test manifold using analytical calculations and CAESAR II simulations in accordance with ASME B31.3. Engineering data, including piping geometry, material specifications, operating conditions, and support configurations, were obtained from project design documents. Sustained and thermal expansion stresses were first estimated using simplified analytical calculations and subsequently verified using CAESAR II simulations. The maximum sustained stress occurred at Node 9100, with analytical and numerical values of 124.00 MPa and 96.70 MPa, respectively, corresponding to a deviation of 28.24%. For the thermal expansion load case, the maximum stress was observed at Node 9320, yielding analytical and numerical values of 2.89 MPa and 2.44 MPa, respectively, with a deviation of 18.45%. These deviations are primarily attributed to the simplified assumptions adopted in the analytical calculations, differences in boundary condition representation, and the more detailed three-dimensional pipe flexibility modeling incorporated in CAESAR II. All calculated stresses remained below the allowable stress limits specified by ASME B31.3 (177.20 MPa for sustained loading and 206.84 MPa for thermal expansion loading). Therefore, the investigated piping system satisfies the code allowable stress requirements under the evaluated sustained and thermal expansion loading conditions. The findings demonstrate that simplified analytical calculations can provide a practical independent engineering verification of numerical simulations during preliminary piping design, while CAESAR II remains essential for comprehensive code-compliance evaluation.